L’ouverture sur le marché africain - Freeman, Linda (Études internationales, 1983)
While in the past, Canada has earned a fairly liberal reputation as it developed political relations with African countries, the trend for the 1980s has been to concentrate on promoting trade and investment. In particular, the interest in expanding markets for Canadian manufactured exports has led to the co-ordination of the Export Development Corporation (EDC) and the Canadian International Development Agency (CIDA) to encourage and support the private sector. As a result, exports to Africa have tripled in the past five years and North Africa (especially Algeria) is becoming a region of major importance for Canadian exporter s. Although in the past the Canadian government has been ambiguous about its approach to promoting trade and investment in white-ruled Southern Africa, it has strengthened its inclination to leave the private sector alone, regardless of the support which Canadian companies are giving to the apartheid system. The before, in the 1980s, Canada's relations with Africa are being increasingly governed by economic imperatives as the government attempts to come to grips with the problems emerging from the economic recession.